Yacon (Smallanthus sonchifolius)-based product increases fecal short-chain fatty acids and enhances regulatory T cells by downregulating RORγt in the colon of BALB/c mice. (April 2019) - Marcon, Letícia De Nadai; de Sousa Moraes, Luís Fernando; Cruz, Bruna Cristina dos Santos; Teixeira, Michelle Dias de Oliveira; Vidon Bruno, Thais Calcagno; Ribeiro, Isabela Egídio; Messias, Anny Caroline; Ferreira, Célia Lúcia de Luces Fortes; de Oliveira, Leandro Licursi; Peluzio, Maria do Carmo Gouveia
Graphical abstract: Highlights: PBY consumption increased fecal humidity and viscosity favoring intestinal transit. PBY consumption is able to increase fecal short-chain fatty acids production. PBY modulates immune response by increasing Treg cell number and decreasing RORγt expression. PBY consumption is able to improve satiety by reducing food intake in mice. Abstract: Although yacon ( Smallanthus sonchifolius ) is a known source of prebiotics (fructooligosaccharides (FOS) and inulin) and phenolic compounds beneficial to gut microbiota and intestinal immune response modulation, its regulatory mechanisms still remain unclear. Therefore, we investigated whether the consumption of a yacon-based product (PBY) modulates the population of intestinal lymphocytes as well as transcription factors that drive host adaptive immune responses. For this purpose, BALB/c male mice were fed either a standard AIN-93M diet or AIN-93M diet supplemented with PBY (6.0% FOS + Inulin) for 8 weeks. We found that PBY consumption in mice reduced food intake, improved fecal humidity and viscosity, intensified fecal short-chain fatty acid production, increased the number of regulatory T cells, and downregulated the expression of RORγt transcription factor in the colon. Thus, it can be inferred from the findings that PBY consumption improves satiety and mucosal integrity, and possibly favors anti-inflammatory immune responses in the colon.